The Association of Platelet and Red Cell Count with Platelet Impedance Changes in Whole Blood and Light-Scattering Changes in Platelet Rich Plasma: Evidence from the Caerphilly Collaborative Heart Disease Study - Sharp, Dan S; Beswick, Andrew D; O'Brien, John R; Renaud, Serge; Yarnell, John W G; Elwood, Peter C (Thrombosis and Haemostasis, 1990)
This epidemiological study was undertaken to explore possible relationships among various haematological indices, prevalent ischaemic heart disease and platelet “function” as measured by two rather different methods. ADP-induced platelet impedance changes in whole blood were strongly associated with prevalent ischaemic heart disease in a general population of 49-66 year men at increased risk. Adenosine diphosphate (ADP) induced platelet aggregation in platelet rich plasma (PRP) at a constant platelet count and also the whole blood platelet count and red cell (RBC) count were strongly and independently related to ADP-induced platelet impedance changes. Both platelet count and platelet aggregation in PRP assessed by changes in optical density were directly related to increasing platelet “sensitivity” as measured by impedance changes in whole blood but RBC count was inversely related. Positive independent relationships between platelet impedance changes and plasma viscosity and fibrinogen were markedly attenuated when platelet count was taken into account, but this finding does not discount a role for these factors in platelet aggregation. No relationship was noted between white blood cell (WBC) count and platelet impedance changes; however, a significant inverse relationship was noted with platelet aggregation in PRP. These findings indicate that laboratory-based experimental findings can be observed in population based studies, and that these haematological factors may be important indicators of ischaemic disease in the population.